The Bedouin divide. (August 2019) - Abu-Kaf, Ghalia; Schejter, Amit; Jafar, Muhammad Abu
Highlights: First-of-its-kind inventory of wireless services available to the Bedouin community. Findings indicate that none of the Bedouin towns are served by the cable industry. Landline penetration among the Bedouin is significantly lower than among Jewish towns. There is a large variation in connectivity levels to broadband among Bedouin towns.